1985
DOI: 10.1159/000238355
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin for Non-Tuberculous Infections?

Abstract: Large populations of rifampicin-sensitive strains of Mycobacterium tuberculosis have been exposed in vitro to changing concentrations of rifampicin (RIF) in line with changes in the blood level of the drug observed during treatment, and to much lower concentrations. Experiments in which the organism was exposed to either 7 or 14 days of cyclically-changing rifampicin concentrations have resulted in the elimination of the M. tuberculosis test strains without the emergence of RIF resistance. The significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Because elevated rifampicin dosages for filariasis cure are predicted in a 1–2 week dose exposure time frame, this is unlikely to result in resistant strains of M tuberculosis (TB), as there is no evidence for rifampicin resistance occurrence when administered for short periods of time 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Because elevated rifampicin dosages for filariasis cure are predicted in a 1–2 week dose exposure time frame, this is unlikely to result in resistant strains of M tuberculosis (TB), as there is no evidence for rifampicin resistance occurrence when administered for short periods of time 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Among various hospital infection control measures [4,6], chemoprophylaxis with rifampin was rec ommended for carriers of outbreak strains of S. aureus among patients and house staff [21,26,32,34], So far, laboratories had to rely on broth or agar dilution test results (determination of minimal inhibi tory concentrations; MICs) with regard to categorization of staphylococcal isolates as susceptible or resistant against rifam pin. This study served to work out tenta tive inhibition zone criteria for the widely employed Bauer-Kirby agar disk diffusion method [5], in order to facilitate screens of clinically isolated S. aureus and CONS strains for susceptibility, intermediate sus ceptibility, or resistance against rifampin [13,14,25,27], Diameter of inhibition zones, mm …”
Section: Introductionmentioning
confidence: 99%
“…Ad dressing this question, Gruneberg et al [3], using an experimental in vitro design in Kirchner' medium, made the experience that, even with a very heavy inoculum size of about 1010 organisms no RIF resis tance did emerge in wild strains of M. tuberculosis, be it with RIF alone or RIF + TMP; these results Chemotherapy 1997;43:451-452 were confirmed in a later publica tion [4], More significantly, papers from the early years of RIF use, when RIF monotherapy was per formed as a part of a trial [5,6], showed that RIF resistance of tu bercle bacilli occurred rather infre quently, but when it did it has not been observed to emerge in less than 3-4 weeks of RIF monothera py. Also, work with staphylococci [7] showed that TMP reduced even in subinhibitory concentrations 10-to 100-fold the frequency of RIFresistant mutants and the mutation rates to RIF alone.…”
mentioning
confidence: 99%